World of Video Clips: Enhancing Critical Thinking Skills in Teaching Theology and Religion in the Classroom - Cordero Jr., Dalmacito (The international journal of religion and spirituality in society, 2021)
A survey from selected Catholic schools in the Philippines shows that Theology is one of the least interesting subjects. With this, the ultimate goal of transmitting Christian values and evangelization seems difficult to achieve. This article presents the relevance of the regular use of video clips as a teaching tool that is integrated with the traditional lecture method. Coupled with proper processing, through the use of thought-provoking questions, this tool enhances the critical thinking skills of the students. The article argues that in a media-oriented society, this practice is relevant and more appealing to college students, especially during the pandemic, when online teaching is in greater use. The technique helps educators to promote active learning and enable students to write good theological reflections that are very useful in their daily life situations.